Determinant of trade costs and their impact on trade flows in ASEAN-5 - Ramli, Mohd. Khairul Rafiz (2013)
Trade costs may have significant impact on trade and can be caused by several factors, such as distance and infrastructural inefficiency. Based on Prabir (2006) and Promfret and Sourdin (2009), the gap between the Cost insurance and freight (CIF) and Free on board (FOB) value of trade flows are useful measure of trade cost in term of consistent volume of trade. Even though the CIF-FOB gap is frequently referred to as transport costs (Hummels 2007), but the magnitude of the trade costs is affected by many variables directly or indirectly (Anderson & Wincoop,2004) Thus, the CIF-FOB measurement is more than freight rates by air or sea but it’s reflect the policy, distance and commodity composition of trade. This study examines the role of infrastructure on trade costs in ASEAN-5 and its impact towards trade flows among member countries namely Malaysia, Indonesia, Philippines, Singapore and Thailand To examine the role of infrastructure toward trade costs, this study adopted a panel data analysis from the period 1980 to 2009, using fixed and random effects model. The results support the findings of the previous studies such as Bernard et al. (1999), Anderson et al. (2001, 2004), Bernard et al. (2003) and Promfret et al. (2009) on distance, Hill (2004) and Coulibaly et al.(2005) on transport infrastructure, Freund et al. (2000), Yi et al. (2005) and Petropoulou (2005) on ICT, and Clark et al. (2001) on port efficiency. The analysis offer evidence that improvement in infrastructure such as paved road and railway routes facilitates the movement of goods from producers to consumers. Our result thus supports the significance of transport infrastructure quality to determine trade costs. Likewise, using fixed and random effects model, the impact of trade costs on trade flows shows asignificant relationship and has the appropriate sign. Based on bilateral data from 1990 to 2010,Gross Domestic Product for exporting and importing country (GDPi) and (GDPj), Endowment (Endo), and Common Border (Combord) are statistically significant. Similarly, for population, exporter country show significant and positive sign. This imply that the higher the population in exporting country, the higher the production of goods thus, the higher the export as well. In contrast, the coefficients for the population of the importer country show a negative and significant result. This indicates that increase in population in importing country will increase the demand of import. There has been solid evident at macroeconomic level that an efficient infrastructure would reduce trade costs and at the same time improves trade flows. This supported by a highly significant in road, rail, sea and air infrastructure coefficient implying that an efficient, secure and integrated transport cooperation among ASEAN members is needed for recognizing the full potential of the Free Trade Area and also for intraregional trade and investment. In addition, a secure and connected information infrastructure is important for supporting the region’s competitiveness and economic growth. Highly significant in ICT infrastructure such as internet and mobile phone that show better information and communication infrastructure that will lead to a reduction in trade costs and increasing the trade flows in this region.